Cytosolic 5′-nucleotidase 1A autoantibody profile and clinical characteristics in inclusion body myositis. Issue 5 (25th January 2017) - Lilleker, J B; Rietveld, A; Pye, S R; Mariampillai, K; Benveniste, O; Peeters, M T J; Miller, J A L; Hanna, M G; Machado, P M; Parton, M J; Gheorghe, K R; Badrising, U A; et al.
Abstract : Objectives: Autoantibodies directed against cytosolic 5′-nucleotidase 1A have been identified in many patients with inclusion body myositis. This retrospective study investigated the association between anticytosolic 5′-nucleotidase 1A antibody status and clinical, serological and histopathological features to explore the utility of this antibody to identify inclusion body myositis subgroups and to predict prognosis. Materials and methods: Data from various European inclusion body myositis registries were pooled. Anticytosolic 5′-nucleotidase 1A status was determined by an established ELISA technique. Cases were stratified according to antibody status and comparisons made. Survival and mobility aid requirement analyses were performed using Kaplan-Meier curves and Cox proportional hazards regression. Results: Data from 311 patients were available for analysis; 102 (33%) had anticytosolic 5′-nucleotidase 1A antibodies. Antibody-positive patients had a higher adjusted mortality risk (HR 1.89, 95% CI 1.11 to 3.21, p=0.019), lower frequency of proximal upper limb weakness at disease onset (8% vs 23%, adjusted OR 0.29, 95% CI 0.12 to 0.68, p=0.005) and an increased prevalence of excess of cytochrome oxidase deficient fibres on muscle biopsy analysis (87% vs 72%, adjusted OR 2.80, 95% CI 1.17 to 6.66, p=0.020), compared with antibody-negative patients. Interpretation: Differences were observed in clinical and histopathological features between anticytosolic 5′-nucleotidase 1A antibody positive and negative patients with inclusion body myositis, and antibody-positive patients had a higher adjusted mortality risk. Stratification of inclusion body myositis by anticytosolic 5′-nucleotidase 1A antibody status may be useful, potentially highlighting a distinct inclusion body myositis subtype with a more severe phenotype.